2008
DOI: 10.1177/159101990801400104
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Head Trauma and Traumatic Aneurysms

Abstract: Subarachnoid hemorrhage following severe trauma to the head is relatively common. In most cases the bleed originates from superficial veins and occasionally from arteries. Following the replacement of cerebral angiography with CT in the diagnostic evaluation of head traumas fewer traumatic aneurysms have been observed. This may indicate that some traumatic aneurysms are missed if angiographic procedures are not performed in patients with severe head injury. Trauma patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This may be due to lower time interval between surgery and PD in the recovery and survivor groups, whereas most other groups started PD later. [2,4] In the current study, the renal function normalized after PD in all surviving patients, and this rate was in consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to lower time interval between surgery and PD in the recovery and survivor groups, whereas most other groups started PD later. [2,4] In the current study, the renal function normalized after PD in all surviving patients, and this rate was in consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…[1,4,13,14] Several studies have attempted to identify the risk factors of ARF requiring RRT in pediatric patients undergoing congenital cardiac surgery. [2,7,14] In consistent with previous studies, [15][16][17] patients who showed recovery of renal function following PD with associated lower CPB and CC times, RACHS-1 category and inotrope scores, BUN and SCr values before PD and a lower time interval between surgery and PD had lower mortality. Additionally, in the present study, higher MAP and CVP scores before PD, late beginning of PD, lower perioperative urine output, and lower diuresis after PD were significant risk factors for increased mortality.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The routine protocol for cerebral trauma MDCT will be supplemented in the near future with routine CT angiography to exclude cerebrovascular injuries, such as traumatic aneurysm, which we believe to be a so far under-diagnosed injury (15).…”
Section: Discussionmentioning
confidence: 99%
“…Results: A total of 10 257 patients with blunt TBI were identified, out of which 459 patients were included in the analysis. Mean age was 47.3 ± 22.5, the majority were male (65.1%) and median ISS was 16 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Thirty-six patients (7.8%) had intracranial aneurysm, of which three patients (0.65%) had TICAs.…”
mentioning
confidence: 99%